A spectacularity concept in modern philosophy; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Kolodiy N. A. Nataliya Andreevna; Khomyakova E. Ekaterina; Kolodiy V. V. Vyacheslav Vladimirovich; Chaika (Chayka) Yu. A. Yuliya Aleksandrovna (2016, 2016)
Title screen